2018
DOI: 10.3390/su10010213
|View full text |Cite
|
Sign up to set email alerts
|

Non-Market Food Provision and Sharing in Japan’s Socio-Ecological Production Landscapes

Abstract: Socio-ecological production landscapes and seascapes (SEPLS) are characterized by a dynamic mosaic of different ecosystem types that maintain relatively high biodiversity and produce a bundle of ecosystem services. One unique characteristic of SEPLS is the sharing of provisioning services within and beyond communities, such as forests, agricultural and marine products. Conventional ecosystem assessments based on statistical data often ignore the benefits of these non-market provisioning services. This short co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…AFNs include practices such as community supported agriculture, farmers' markets, organic farms, cooperatives, solidarity purchasing groups, farm shops, urban agriculture, box scheme, and community gardens [2]. The distribution of nonmarket food (home grown foods and foods received from neighbors and/or relatives [3][4][5][6][7]) can be considered one aspect of AFNs that is related to the previously described characteristics [1]. Further, studies on urban gardening, home gardening, and community gardening can be seen in other works [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…AFNs include practices such as community supported agriculture, farmers' markets, organic farms, cooperatives, solidarity purchasing groups, farm shops, urban agriculture, box scheme, and community gardens [2]. The distribution of nonmarket food (home grown foods and foods received from neighbors and/or relatives [3][4][5][6][7]) can be considered one aspect of AFNs that is related to the previously described characteristics [1]. Further, studies on urban gardening, home gardening, and community gardening can be seen in other works [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The vegetable receiving frequency in the rural and suburban areas was higher than in the urban area. Previous studies reported no significant difference in the ratio of access to nonmarket food because of the agricultural area classification [4,7]. However, there were significant relationships between land use types and the amounts and variety of nonmarket foods individuals consumed [7].…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies reported no significant difference in the ratio of access to nonmarket food because of the agricultural area classification [4,7]. However, there were significant relationships between land use types and the amounts and variety of nonmarket foods individuals consumed [7]. In the initial analysis of Survey 2, more people were growing vegetables in rural and suburban areas compared to urban areas [27].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations